Strengths and limitations of using 18fluorine-fluorodihydroxyphenylalanine PET/CT for congenital hyperinsulinism. Issue 5 (September 2014) - Montravers, Françoise; Arnoux, Jean-Baptiste; Ribeiro, Maria-Joao; Kerrou, Khaldoun; Nataf, Valérie; Galmiche, Louise; Aigrain, Yves; Bellanné-Chantelot, Christine; Saint-Martin, Cécile; Ohnona, Jessica; Balogova, Sona; Huchet, Virginie; et al.
<x xml:space="preserve">Abstract</x> 18fluorine-fluorodihydroxyphenylalanine (FDOPA) PET/CT is currently the first-line imaging technique to distinguish between focal and diffuse forms of congenital hyperinsulinism (CHI) and to accurately localize focal forms. However, this technique has a number of limitations, mainly the very small size of focal forms or inversely a very large focal form mimicking a diffuse form, and misinterpretation of physiologic uptake masking hot spots or inversely mimicking focal forms. The other limitation is the limited availability of the radiopharmaceutical. FDOPA PET/CT has no recognized competitor to date among the available morphologic and functional imaging techniques. Other potential approaches using specific tracers for positron emission tomography (PET) are discussed, using radiopharmaceuticals specific for β cell mass or targeting somatostatin receptors. These radiopharmaceuticals can be labeled with gallium-68, a PET emitter readily available in PET centers equipped with 68Ge/68Ga generators.